The population and tribe status of the Arabian Peninsula at the beginning of the twelfth century AH / the eighteenth century AD - البودي مازن (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research deals with the demographics of the Arabian Peninsula under the Ottoman domination, prior to the rise of the Wahhabi movement, which later took control of the region, speaking at the beginning of the geographical location and its importance. The research also deals with the distribution of the Arab tribes in the Najd and Hijaz region, and the relations between them, which can be described as hostile relations and struggle over the overlapping of their borders and their different lineages.